2023
DOI: 10.1177/0271678x231162184
|View full text |Cite
|
Sign up to set email alerts
|

RNA profiling of sEV (small extracellular vesicles)/exosomes reveals biomarkers and vascular endothelial dysplasia with moyamoya disease

Abstract: The association of exosomal RNA profiling and pathogenesis of moyamoya disease (MMD) and intracranial Atherosclerotic disease (ICAD) is unknown. In this study, we investigated the RNA profiles of sEV (small extracellular vesicles)/exosomes in patients with MMD and ICAD. Whole blood samples were collected from 30 individuals, including 10 patients with MMD, 10 patients with ICAD, and 10 healthy individuals. Whole transcriptome analysis was performed using the GeneChip WT Pico Reagent kit. Transcriptional correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Cao et al found that activin receptor-like kinase 7 promotes VSMC apoptosis by activating the Smad2/3 signaling in diabetic atherosclerosis ( Cao et al, 2022 ). These studies provided evidence that SMAD2 downregulation in patients with MMD might promote angiogenesis, proliferation and phenotype switching of VSMCs, which are the important characteristics of MMD mentioned before ( Ma et al, 2022 ; He et al, 2023c ; He et al, 2023d ). As for the results in our study, pathway enrichment analysis also showed that SMAD2 was enriched in the Notch, GAP junction, and toll-like receptor signaling pathways, which are also associated with angiogenesis, vascular development, endothelial cell and VSMC growth in previous studies ( Beyer and Berthoud, 2018 ; Shafeghat et al, 2022 ; Cuervo et al, 2023 ).…”
Section: Discussionsupporting
confidence: 56%
“…Cao et al found that activin receptor-like kinase 7 promotes VSMC apoptosis by activating the Smad2/3 signaling in diabetic atherosclerosis ( Cao et al, 2022 ). These studies provided evidence that SMAD2 downregulation in patients with MMD might promote angiogenesis, proliferation and phenotype switching of VSMCs, which are the important characteristics of MMD mentioned before ( Ma et al, 2022 ; He et al, 2023c ; He et al, 2023d ). As for the results in our study, pathway enrichment analysis also showed that SMAD2 was enriched in the Notch, GAP junction, and toll-like receptor signaling pathways, which are also associated with angiogenesis, vascular development, endothelial cell and VSMC growth in previous studies ( Beyer and Berthoud, 2018 ; Shafeghat et al, 2022 ; Cuervo et al, 2023 ).…”
Section: Discussionsupporting
confidence: 56%
“…Previous research has provided valuable insights into the distinct patterns of exosomal RNA expression that are associated with the pathogenesis of MMD [ 17 ]. Specifically, the upregulation of IPO11 and PRMT1 circRNAs has been linked to the promotion of angiogenesis in MMD, while the underexpression of CACNA1F circRNA is associated with vascular occlusion.…”
Section: Sample Size Calculationmentioning
confidence: 99%